Erythema nodosum‐like panniculitis mimicking disease recurrence: A novel toxicity from immune checkpoint blockade therapy—Report of 2 patients. (13th October 2017) - Tetzlaff, Michael T.; Jazaeri, Amir A.; Torres‐Cabala, Carlos A.; Korivi, Brinda R.; Landon, Genie A.; Nagarajan, Priyadharsini; Choksi, Adrienne; Chen, Leon; Uemura, Marc; Aung, Phyu P.; Diab, Adi; Sharma, Padmanee; et al.
Abstract : Immunotherapies targeting cytotoxic T‐lymphocyte‐associated antigen 4 (CTLA‐4) and the programmed cell death 1 (PD‐1) receptor and its ligand (PD‐L1) have showed substantial therapeutic benefit in patients with clinically advanced solid malignancies. However, autoimmune toxicities are common and often significant adverse events with these agents. While rash and pruritus remain the most common cutaneous complications in treated patients, novel dermatologic toxicities related to immune checkpoint blockade continue to emerge as the number of patients exposed to immunotherapy increases. Here, we describe 2 patients treated with combination immunotherapy with ipilimumab and nivolumab who developed painful subcutaneous nodules. Although the findings were clinically concerning for disease recurrence, histopathologic examination of biopsies from the lesions revealed a subcutaneous mixed septal and lobular erythema nodosum‐like panniculitis. Notably, neither patient received immunosuppressive therapy for these lesions, which subsequently remained stable, and both patients' cancer remained controlled. These cases show that the dermatologic toxicity profile of immune checkpoint blockade is diverse and continues to expand, and illustrates that recognition of such toxicities is critical to optimal patient management.